2015
DOI: 10.1080/09205063.2015.1100495
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of electrospun poly(caprolactone) fibers for pH-controlled delivery of doxorubicin hydrochloride

Abstract: Functionalized electrospun polymer fibers are a promising candidate for controlled delivery of chemotherapeutic drugs to improve the therapeutic efficacy and to reduce the potential toxic effects by delivering the drug at a rate governed by the physiological need of the site of action. In this study, poly(caprolactone) (PCL) fibers were fabricated by electrospinning, followed by hydrolyzation to introduce functional groups on the fiber surface. Characterization studies were performed on these functionalized fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…This could be due to more DOX being released from scaffolds subjected to an acidic media of pH 6.0 as compared to normal tissue pH 7.2. [22] The residual DOX content analysis done on the scaffolds shows that approximately 59% DOX was released from scaffolds subjected to pH 7.2 and approximately 68% was released from scaffolds subjected to pH 6.0. This roughly corresponds to 14 μM DOX concentration to which cells were subjected to at pH 7.2 and 17 μM DOX concentration for cells at pH 6.0.…”
Section: In Vitro Drug Release From Composite Scaffoldsmentioning
confidence: 96%
See 1 more Smart Citation
“…This could be due to more DOX being released from scaffolds subjected to an acidic media of pH 6.0 as compared to normal tissue pH 7.2. [22] The residual DOX content analysis done on the scaffolds shows that approximately 59% DOX was released from scaffolds subjected to pH 7.2 and approximately 68% was released from scaffolds subjected to pH 6.0. This roughly corresponds to 14 μM DOX concentration to which cells were subjected to at pH 7.2 and 17 μM DOX concentration for cells at pH 6.0.…”
Section: In Vitro Drug Release From Composite Scaffoldsmentioning
confidence: 96%
“…[20] The amenability of zebrafish to pharmacological testing and superior imaging properties of fish tissues that allow visualization of cancer progression and angiogenesis in live animals makes it an attractive animal model choice for cancer research. [21] In our previous publication, [22] we have shown that hydrolysis of electrospun PCL scaffolds leads to the generation of functional groups (-COOH) on the fiber surface that can be utilized to ionically bind DOX at a certain pH (~ 17,000 ng/mg drug payload). The change in pH would result in disruption of ionic bonds between the two and the drug would be released from these scaffolds at an acidic pH.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of drug delivery systems has been a common strategy for enabling controlled drug delivery at the targeted site . A number of research using individual or a combination of surface modifications has been carried out on electrospun fibers to control the release of immobilized anticancer drugs whilst preserving functionality.…”
Section: Electrospun Nanofibers For Chemotherapymentioning
confidence: 99%
“…Liu et al fabricated electrospun fibers containing amine functional surface using polyurethane, 3-aminopropyltriethoxysilane, and utilized the charged functional groups (pH 3-5) -NH 3 + and -COO À for the adsorption of silver nanoparticles through electrostatic interaction [83]. Jassal et al fabricated PCL electrospun fibers, immobilized doxorubicin on hydrolyzed PCL fibers, and proved that doxorubicin drug adsorption on electrospun fibers is strongly pH dependent [84]. Various parameters such as surface charge, topography, roughness pH, and ionic strength of the ESM environment control the adsorption of drugs and nanoparticles.…”
Section: Noncovalent Immobilization Techniquementioning
confidence: 99%